Reclaiming the mainstream individualist feminism rediscovered - Taylor, Joan Kennedy (Prometheus Books, 1992)
At a time when some feminist critics are saying that the feminist movement has been too individualistic and too market oriented, Joan Kennedy Taylor contends that feminists should cherish and celebrate their tradition of individualism and equal rights. Reclaiming the Mainstream points out that the most enduring voices in the women's movement--the voices that each successive generation of feminists rediscovers with a shock of recognition--Mary Wollstonecraft, Margaret Fuller, John Stuart Mill, Charlotte Perkins Gilman--have spoken out against government privileges and special protection for women so that their individual differences might flourish. This book argues that modern feminism grew out of the nineteenth-century Woman Movement, which, like much late nineteenth-century thinking, became a battleground between individualist and collectivist ideas
Keywords: Geschichte; Feminism -- United States; Individualism -- United States; Women's rights -- United States; Feminismus; Individualismus; Frauenbewegung; USA